TEACHER’S QUESTION IN TEACHING READING NARRATIVE TEXT - Sere Nidya Damanik; Masitowarni Siregar; Farida Hanim Saragih (Universitas Negeri Medan, 2019)
Teacher’s questions play an important role in the classroom interaction. This study was conducted to investigate the levels of question that English teacher used while teaching narrative text. The subject of this study was an English teacher of SMA Gajah Mada. The data were collected by observing and recording while the teacher was teaching in two different meetings and also by interviewing the teacher. The research design of this study was qualitative research. The study reveals that the total number of the question was 63 questions that asked by the teacher. There were Low Cognitive Questions (LCQ); 48 (76%) remembering questions, 13 (21%) understanding questions, 0 (0%) applying questions and High Cognitive Question (HCQ); 0 (0%) analyzing questions; 2 (3%) evaluating questions, and 0 (0%) creating questions. LCQ questions are dominantly used by the teacher. Keywords: Reading Narrative Text, Teacher’s